2006
DOI: 10.1159/000104859
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Autoimmune Thyroid Diseases

Abstract: Autoimmune thyroid diseases (AITD) are the far most common autoimmune disorders, their prevalence in Western countries exceeding 5% of the general population. In the large majority of individual cases the clinical impact of AITD is not severe, however, their widespread diffusion renders them a significant health problem. AITD are heterogeneous in their clinical presentation: the two main forms are autoimmune thyroiditis (AT) and Graves’ disease (GD). Although they probably share, at least in part, a common gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 99 publications
3
14
0
2
Order By: Relevance
“…A review of the literature including seven case-control studies has highlighted the preexistence of a 'negative' stressful event in patients with Graves' disease (8,9,10,11,12,13,14,15). However, one can criticize the principle of case-control studies: it is difficult to assess the effect of a given stressful event in different individuals; the validity of filling out a questionnaire may be limited in an emotional context, the actual date of the onset of the disease is difficult to specify and nothing proves that it occurred after the stressful event (8). However, a prospective study conducted in Serbia shows that while the incidence of Graves' disease had been stable since 1971, it increased significantly between 1992 and 1995, i.e.…”
Section: Epidemiological Data On Stress and Graves' Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature including seven case-control studies has highlighted the preexistence of a 'negative' stressful event in patients with Graves' disease (8,9,10,11,12,13,14,15). However, one can criticize the principle of case-control studies: it is difficult to assess the effect of a given stressful event in different individuals; the validity of filling out a questionnaire may be limited in an emotional context, the actual date of the onset of the disease is difficult to specify and nothing proves that it occurred after the stressful event (8). However, a prospective study conducted in Serbia shows that while the incidence of Graves' disease had been stable since 1971, it increased significantly between 1992 and 1995, i.e.…”
Section: Epidemiological Data On Stress and Graves' Diseasementioning
confidence: 99%
“…Conversely, thyroid hormones potentiate the effects of glucocorticoids and catecholamines. Therefore, there is a 'cross-talk' between the two axes, and a disruption resulting from an excessive secretion of thyroid hormones during thyrotoxicosis can lead to vicious circles between thyroid homeostasis and immune response (8).…”
Section: Hormonesmentioning
confidence: 99%
“…It has been demonstrated that stress affects the immune system and can cause increased susceptibility to tumors [16][17][18] , infections [19][20][21] , and autoimmune diseases [22][23][24] . Therefore, determination of the protein and peptide composition during stress on the immune system may not only lead to an improved understanding of stress, especially in regard to psychosomatic illness, but may also offer new insights into the possibility of using selected peptides or proteins as markers of processes occurring during stress to explain the molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы значительно выросло количество исследовательских работ, посвященных изучению эффектов стресса на функцию щитовидной железы (ЩЖ) и периферический метаболизм тиреоидных гормонов [1][2][3][4]. Это может быть обусловлено, по-видимому, несколькими составляющими.…”
Section: ли надольникunclassified